European consultation-liaison services and their user populations: the European Consultation-Liaison Workgroup Collaborative Study - Huyse, F (2010)
The authors identified variations in the characteristics of patients referred to 56 consultation-liaison (C-L) services in 11 European countries. The authors found differences in the types of patients referred to the services, and there were significant differences between countries. The first difference lays in whether services saw patients for deliberate self-harm and for substance abuse. German psychosomatic C-L services saw virtually no such patients, although in other C-L services these patients constituted one-quarter to one-third of the patients referred. The second difference lays in the remaining group of referred patients. This group is best characterized by two dimensions. One describes the severity of psychopathology -- ranging from organic mental conditions to somatization. The other describes the clarity of the physical diagnosis -- ranging from patients referred by surgical wards to those referred by general medicine and neurology wards.